Community is more than just a physical space: Discuss this statement with specific reference to the role of the concept and experience of contemporary community - Schranz, Edit (METSZETEK Társadalomtudományi Folyóirat, 2022)
What happens if among the members of a society and among the smaller and larger units and groups making up the society trust and confidence seems to be disappearing at once? What happens if confidence reposed into each other fall victim to social differences as well as to the economic / cost-of-living boxing of modern information society? How to stop the crisis symptom that seems to be developing this way and which is shown in the fragmentation of communities?1 With other words, is it possible to “stick again together” a community or even a whole society started to disintegrate? The questions, even if not so characteristically phrased, provide sociologists actually with the scope of understanding our modern, individualistic world (Habermas 1994). Gusfield (1975) depicts dichotomy of community and society in a way that we should interpret community as a pervading, significant contrast. By now literature seems as if it was only be able to picture the changes taking place in the images both of the society and community describing them by even more pronounced, contradictory processes. The changes that send messages on the disintegration of categories and frames becoming insecure instead of the security and integration quasi missed by Habermas. It also seems as if—quasi as an answer given to this process—occlusion/seclusion both on the part of community members and the various communities from the seemingly unknown and insecure changes were more intensive (Légmán 2012). We intend to construe these phenomena on the next pages, but due to extension limits without the need for completeness of social interpretations. We want to do it with the help of mainly one dimension: value preference through the example of a given society, namely the Hungarian one. Thus we get to the stability and the solidarity of the members of the smallest unit of society, one which accepts and expresses various value preferences, the family.